Home, but Left Alone: Time at Home and Child Abuse and Neglect During COVID-19. (February 2023) - Bullinger, Lindsey Rose; Boy, Angela; Feely, Megan; Messner, Stephen; Raissian, Kerri; Schneider, William; Self-Brown, Shannon
We use high-frequency mobile phone movement data and quick-release administrative data from Georgia to examine how time at home during the COVID-19 pandemic is related to child maltreatment referrals. Findings show that referrals plummeted by 58% relative to previous years, driven by fewer referrals from education personnel. After this initial decline, however, each 15 minutes at home was associated with an increase in referrals of material neglect by 3.5% and supervisory neglect by 1%. Our results describe how children have fared during the initial wave of the pandemic, and the results have long-term implications for child development and well-being.